Equity incentives and earnings management: Evidence from the banking industry - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2011)
We examine the relationship between equity incentives and earnings management in the banking industry. By focusing on this regulated industry and using industry-specific earnings management proxies, we provide evidence on the impact of regulation on earnings management arising from chief executive officers' equity incentives. We find that bank managers with high equity incentives are more likely to manage earnings, but only when capital ratios are closer to the minimums required by regulators. This finding indicates that, in the banking industry, potential regulatory intervention induces, rather than mitigates, earnings management arising from equity incentives.